2016
DOI: 10.1089/tmj.2015.0155
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Telestroke During Ambulance Transport Is Feasible in a Rural EMS Setting: The iTREAT Study

Abstract: In this small, single-centered study we maintained high-quality continuous video transmission along primary ambulance corridors using a low-cost mobile telemedicine platform. The system is designed to be portable and adaptable, with generalizability for rapid assessment of emergency conditions in which direct observational exam may improve prehospital diagnosis and treatment. Thus mobile telestroke assessment is feasible using low-cost components and commercial wireless connectivity. More research is needed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 34 publications
0
41
0
1
Order By: Relevance
“…119 More recent studies examined the paradigm again and showed that the transmission of video data reached acceptable levels of quality and reliability. 118,120 However, the most compelling evidence comes from the STEMO (Stroke Emergency Mobile) project in Berlin in which the use of a mobile stroke unit with onboard neurologist but remote teleradiologist has led to more rapid alarm-to-needle times with no increase in the rate of complications and improvement in outcomes estimated at €32 456 per quality-adjusted life-year. 121,122 In the United States, several ongoing pilot studies of mobile stroke units suggest that the model is robust and that a teleneurologist may be able to substitute for an onboard neurologist.…”
Section: Mobile Stroke Unitsmentioning
confidence: 99%
“…119 More recent studies examined the paradigm again and showed that the transmission of video data reached acceptable levels of quality and reliability. 118,120 However, the most compelling evidence comes from the STEMO (Stroke Emergency Mobile) project in Berlin in which the use of a mobile stroke unit with onboard neurologist but remote teleradiologist has led to more rapid alarm-to-needle times with no increase in the rate of complications and improvement in outcomes estimated at €32 456 per quality-adjusted life-year. 121,122 In the United States, several ongoing pilot studies of mobile stroke units suggest that the model is robust and that a teleneurologist may be able to substitute for an onboard neurologist.…”
Section: Mobile Stroke Unitsmentioning
confidence: 99%
“…[5][6][7][8] Emergency medical services' (EMS) identification of likely strokes helps, 9,10 and in-ambulance teleneurology has been considered but not tested clinically. 11,12 Mobile stroke transport units (MSTUs), computed tomographic scanner-equipped ambulances with a neurologist, either in person or by telemedicine, 8 to assess thrombolytic appropriateness and oversee treatment, in the prehospital setting, decrease treatment time 25 minutes. 5,8 However, MSTUs cost US$0.75M to $1.4M 5 and require a computed tomographic technologist, an emergency medical technician, and a licensed healthcare practitioner to administer medication, incurring operating costs that can exceed US$1M/y.…”
mentioning
confidence: 99%
“…In preparation for the study, investigators mapped cellular connectivity, distance, and transport times along ambulance routes triaging to the receiving hospital, UVA Medical Center. 13 To ensure optimization of mobile broadband during ambulance transport, we partnered with Verizon Wireless, the largest supplier of 4G LTE coverage in the region. We targeted 9 minutes of continuous connectivity to allow for completion of a focused neurologic examination using the NIHSS in the field.…”
mentioning
confidence: 99%
“…Initial system development and feasibility testing have been presented elsewhere. 13 During the simulation study, the system included an Apple iPad with retina display (2,048-by-1,536 resolution at 264 pixels per inch), cradled mount, 4G LTE CradlePoint modem with Verizon 4G Mini SIM (Subscriber Identification Module) card, and externally mounted cellular antennae. For live video streaming, we used the Cisco Jabber (Movi) videoconferencing application, which enables encrypted bidirectional telecommunication and meets security standards for transmission of protected health information-HIPAA (Health Insurance Portability and Accountability Act) secure and firewall protected through a virtual private network.…”
mentioning
confidence: 99%
See 1 more Smart Citation